An economic study on maize residue practices in Dinajpur district (Journal of the Bangladesh Agricultural University, 2017)
The study was conducted to examine the maize residue practices and its impact on productivity, profitability on succeeding crop and farmers livelihood. A total of 60 farmers from Ghoraghat upazila of Dinajpur district were selected randomly for data collection. Descriptive statistics (i.e., sum, average, percentages, ratios, etc.), profitability analysis and logit model were employed to achieve the objectives. In case of pattern of maize residue retention, whole retention method was the highest and it was 78.2 percent. The whole retention of maize residue was found higher in far distance plots from homestead and it was 82.8 percent. The highest utilization of maize residue was identified as organic fertilizer and it was 82.2 percent. Due to maize residue practices, both crop and livestock were benefited through resource interdependences. The productivity, profitability and annual income of succeeding crop i.e., Aman rice were higher due to maize residue practicing. The result of logit regression model shows that the farm size, age of household head, farm income and non-farm income were found as significant variables in explaining the maize residue adoption. The access on human capital, social capital, financial capital, natural capital and physical capital were increased by 23.5, 22.7, 26.7, 10.6 and 18.8 percent, respectively due to the practice of maize residue in comparison to traditional farming. The study recommended that farmers could enhance their livelihood if they get proper training facilities and extension services for maize residue management.J. Bangladesh Agril. Univ. 14(2): 209-218, December 2016